On Techno-Tantrik Embodiment. Issue 1 (March 2023) - Bedos, Clémentine
Abstract : Inspired by Paul B. Preciado's work of autotheory, Testo Junkie, and the various processes of self-shaping that circulate through his corpus, this visual piece and its accompanying personal essay draw upon the artist's familial and ancestral knowledge of their grandmother's confinement in an asylum. Developing a visual methodology based on the holographic philosophy of Nondual Śaiva Tantra, Techno-Tantrik Embodiment seeks to offer analogous holistic technologies that harness the power of the repressed and the taboo, to transform mind, body and environment. The piece questions how technological scale sets conditions for relations, feelings, democratic processes and infrastructures, and it provides a mixed-reality approach to consciousness, asking: what types of engagement with image-based systems can subvert and transform our worldview? Utilizing a queer framework that eschews respectability or a quest for 'positive' counternarratives, it explores the possible synergies between Tantrik and digital technologies, to build meaningful connections with ourselves and alterity.